Business prospects and challenges in Haor areas of Bangladesh: Business prospects and challenges in Haor areas (Journal of the Bangladesh Agricultural University, 2019)
Bangladesh has experienced promising improvements in its overall economic, social and health conditions, but the progress is not up to the mark in Haor areas. Improvements in this sector can lead to increase in production, employment and poverty reduction. Aside from increased productivity, farmers need a supporting business environment where availability and access to agricultural inputs are ensured, fair returns to investment are secured. Keeping these issues in mind, the study was conducted to measure productivity, profitability, and price variation of inputs and outputs; and to identify business challenges and suggest policy options for overcoming constraints and exploring intervention strategies in Haor regions. Primary data were collected from Mohongonj upazila of Netrakona district and Mithamoin upazila of Kishoregonj district. A total of 120 farmers and 24 service providers were interviewed for data collection. Face-to-face interview, focus group discussions (FGD) and key informant interviews (KII) were conducted to collect primary data. For analyzing the data, descriptive statistics and accounting method were used to achieve the objectives. The study revealed that average farm size of the respondents was 0.73 hectare. Most of the farmers (39.2%) followed the farming system of crop-livestock-fish catching (C-L-F). Fish catching was the most profitable enterprise with BCR 2.12. The differences in productivity of crop farming and poultry rearing between Haor areas and main land were found statistically significant. Remarkable differences in quantity and price of inputs and outputs were seen in Haor areas and main land. Favorable farm environment and proper utilization of agricultural resources were identified as major strength and opportunity in the study areas. Formation of agribusiness clusters involving input suppliers, credit/financial organizations and different support service providers will result in more income, better nutrition and improved livelihood of the Haor people. The study concludes that the business environment in the Haor areas has a high potential to be exposed with the integration of available local agricultural resources. Government price support and improved market management are recommended for accessibility and appropriate use of agricultural inputs, and for managing local productive resources in use of business prospects in the study areas.J. Bangladesh Agril. Univ. 17(1): 65–72, March 2019